Resilience capacity of the coffee agroecosystems in Tezonapa, Veracruz, Mexico - Quiroz Guerrero, Ismael; Pérez-Vázquez, Arturo; Landeros Sánchez, Cesáreo; Gallardo López, Felipe; Velasco Velasco, Joel; Benítez Badillo, Griselda (Agronomía Mesoamericana, 2024)
Introduction. The coffee agroecosystems holds significant environmental, social, and economic importance in the subtropical regions of Mexico, but it is vulnerable to unexpected events such as climate change. In recent history, it has been documented that the coffee agroecosystem undergoes a constant process of self-organization based on adaptation and learning in the face of various adverse scenarios. Objective. To determine the resilience capacity of the coffee agroecosystem in the central region of the Veracruz state. Materials and methods. The research was conducted from December 2017 to November 2018 in Tezonapa, Veracruz, Mexico. Fifty-two interviews were conducted with coffee growers to measure the resilience index, which is composed of thirty variables corresponding to seven factors (social, economic, technological, infrastructure, communications, institutional, and environmental). These factors were normalized using the mim-max scaling method. Resilience was estimated on a scale of 0-1, where values close to zero represent low resilience capacity and values close to one, represent high resilience. The data were analyzed using descriptive statistics, Kruskal-Wallis tests, and Chi-squared tests. Results. Statistically significant differences (p<0,05) were found for the economic (0,06) and technological (0,22) dimensions indicators, which had the lowest contribution to resilience. Conversely, the social (0,78) and environmental (0,74) dimensions had a the highest contribution to resilience capacity, determined by the altitudinal gradient. Conclusion. The indicators that contributed the most to the resilience capacity of the coffee agroecosystem were those in the social and environmental dimensions, while the economic and technological dimensions contributed the least.